Punching shear strengthening of flat slabs: CFRP and shear reinforcement - Moreno, Carlos (2015)
Punching in slabs is usually associated to the application of concentrated loads or to the presence of columns. One of the main concerns related to flat slabs is its punching shear capacity at slabcolumn connection, which is subjected to a very complex three-dimensional stress state. Provided that bending capacity is installed, punching shear failure is hence characterized by the development of a truncated cone shaped surface at the slab-column connection. The experimental programme carried out by the authors includes four normal strength concrete slabs (1100×1100×100 mm3), with and without shear reinforcement, submitted to punching under a concentrated load. One of the specimens included typical bent-down bars as shear reinforcement. Frequently, there is the need to strengthen existing flat slabs against punching shear failure. Current paper intends to further investigate the structural response of such reinforcement techniques. One of the strengthening practices, which have been tested within current experimental programme, consists on gluing carbon fibre reinforced polymers on concrete surface. Moreover, the near surface mounted technique has also been tested within current experimental work. Finally, a fourth specimen served as reference. The effects of shear reinforcement and of the carbon fibre reinforced polymers enhancing punching shear capacity are observed.